Pengaruh Cash Rasio dan Debt to Asset Rasio terhadap Return of Asset PT Enam Lima Ihsan 2018-2023 - Arinta Meylinda; Amin Setio Lestiningsih; Intan Kusuma Dewi (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2024)
The rapid development of information technology has increased the need for financial information, especially in the business world. The purpose of this study is to determine how the effect of Return On Asset (financial performance) on PT Enam Lima Ihsan in2018 - 2023 based on financial ratios, namely Cash Ratio and Debt to Asset Ratio on Return On Asset (ROA). This company is engaged in the General and Service Sector with an emphasis on Information Technology Solutions, data collection methods obtained from various existing sources. This research is descriptive quantitative with IBM SPSS 27 software. The results of this research test are based on the partial test (T) which shows that the Cash Ratio value of 0.088 > 0.05, which means that the Cash Ratio is positive and does not have a significant partial effect on Return On Asset (ROA) and the Debt to Asset Ratio value of 0.440 > 0.05, which means that the Debt Toll Asset Ratio does not have a significant partial effect on Return On Asset (ROA). Based on the simultaneous test (f) Cash Ratio and Debt to Asset Ratio, the value is 0.017 where 0.017 < 0.05 so Hol is rejected and Ha is accepted, which means that Cash Ratio and Debt to Asset Ratio simultaneously have a positive and significant effect on Return on Assets (ROA).